The Impact of Digital Divide on the Economic Development of Ukrainian Regions in the Conditions of War - Tomashevska, Т. V. (Statistics of Ukraine, 2025)
The impact of digital divide on the economic development of Ukrainian regions in the conditions of war was explored using principal component analysis and Cobb-Douglas production function. The importance of this study is caused by the need to overcome the uneven access of the population to advanced information & communication technologies, which is becoming a critical factor of the socio-economic resilience of the regions facing the crisis-related challenges. The research objective is to assess the relationship between the development of digital infrastructure, human capital and gross regional product by Ukrainian region. A set of indicators measuring the economic and digital performance in the regions was created. It included investment in telecommunications, employment in the telecommunication sector, number of researchers, number of university students, number of localities with access to fixed-line Internet, number of households with access to fixed-line Internet per 100 households. Principal component analysis was used to reduce dimensionality of data and identify main vectors of change. Using scree diagrams revealed that the first two principal components explained 82.9% of the overall dispersion, allowing to focus on them in further analysis. While the first component mostly describes investment and employment in the telecommunication sector, the second one describes the accessibility of digital services for the population. Cobb-Douglas production function built on the basis of the derived principal components allowed to assess the relationship between digital factors and gross regional product. Results of the modelling showed an essential positive impact of the factors related with investment in digital infrastructure and human capital on the economic development of the regions. Based on two principal components, Cobb-Douglas production function showed a high explanatory power (R² = 0,754). The results give evidence that the regions with a high level of digital facilities and employment in the telecommunication sector demonstrate a better economic performance even in the conditions of martial law. This confirms that the development of digital infrastructure and support of human capital are crucial to the economic resilience of the regions. The article ends with the author’s recommendations for public administration bodies about regional digital policy setting with consideration to the revealed patterns.